Water-soluble humic acid quantification using a flow-injection system with and without sample pretreatment - Palomeque, Miriam Edid (2013)
Two automated methods for the determination of humic acids (HAs) in natural water samples are presented. Flow injection systems were developed based on the formation of a complex between humic acids and toluidine blue dye. When the complex is formed, the dye absorbance signal decreases at selected operating conditions. Method A, without sample pretreatment, presents a linear calibration curve over HA concentration range 1.14−35.0 μg mL−1 , with a limit of detection (LOD) of 0.4 μg mL−1 (3 Sy/x) and a sample throughput of 80 h−1 . To determine lower HA concentration levels, a preceding separation/preconcentration step was included (method B). This method has a linear range of 1.5−20.0 μg mL−1 and a sample throughput of >8 h−1 and could detect humic substances at a concentration of 0.05 μg mL−1 after a 4-min retention time. The RSDs for methods A and B calculated using the slopes of seven independent calibration graphs obtained on different days and with different conditions (standard solution, reagent solution, etc.) were 4.5% and 4.2% respectively. Both methods were satisfactorily applied to natural water samples, with recovery percentages in the 95−107% range, and compare very well with other methods.